RESPONSE OF SENSITIVE CORN HYBRIDS TO THE ASSOCIATION OF NICOSULFURON AND TIMING OF NITROGEN APPLICATION - Heitor Franco de Sousa; Paulo César Timossi; Antônio Paulino da Costa Netto; Claudio Hideo Martins Costa (Ciência Agrícola, 2019)
Nicosulfuron is an herbicide used in corn crop for controlling weeds, some hybrids are sensitivity to nicosulfuron even more when it is applied near to the application of nitrogen fertilizers. Thus, this study aimed to evaluate the response of sensitive corn hybrids to association of urea and coated urea applied near to nicosulfuron application on V4 corn stage. P 3646 hybrid was the most sensitive, and urea and coated urea applied near to nicosulfuron had significant effect on corn growth for all hybrids. Most hybrids showed high or significant (p < 0.10) correlation coefficients for grain yield, cob length and row per ear. SYN 7341 hybrid was the one that showed better results in grain yield with urea and nicosulfuron combination. Coated urea should not be applied after V8corn stage when nicosulfuron is applied at V4.